A conceptual model of water yield effects from beetle‐induced tree death in snow‐dominated lodgepole pine forests. Issue 14 (24th May 2012) - Pugh, Evan; Gordon, Eric
Abstract In regions of western North America with snow‐dominated hydrology, the presence of forested watersheds can significantly influence streamflow compared to areas with other vegetation cover types. Widespread tree death in these watersheds can thus dramatically alter many ecohydrologic processes including transpiration, canopy solar transmission and snow interception, subcanopy wind regimes, soil infiltration, forest energy storage and snow surface albedo. One of the more important causes of conifer tree death is bark beetle infestation, which in some instances will kill nearly all of the canopy trees within forest stands. Since 1996, an ongoing outbreak of bark beetles (Coleoptera: Scolytidae) has caused widespread mortality across more than 600, 000 km2 of coniferous forests in western North America, including numerous Rocky Mountain headwaters catchments with high rates of lodgepole pine (Pinus contorta) mortality from mountain pin beetle (Dendroctonous ponderosae) infestations. Few empirical studies have documented the effects of MPB infestations on hydrologic processes, and little is known about the direction and magnitude of changes in water yield and timing of runoff due to insect‐induced tree death. Here, we review and synthesize existing research and provide new results quantifying the effects of beetle infestations on canopy structure, snow interception and transmission to create a conceptual model of the hydrologic effects of MPB‐induced lodgepole pine death during different stages of mortality. We identify the primary hydrologic processes operating in living forest stands, stands in multiple stages of death and long‐dead stands undergoing regeneration and estimate the direction of change in new water yield. This conceptual model is intended to identify avenues for future research efforts. Copyright © 2012 John Wiley & Sons, Ltd.